A Revisionist Approach to the Marxist Concept of Revolution - Malay Jr., Armando (Kasarinlan: Philippine Journal of Third World Studies, 2009)
Comments on the Manifesto Papers. Calling for revolution, 150 years after the Manifesto, is not an innocent act. Yet one can well understand how certain durable features of the Philippine sociopolitical landscape can tempt even peaceful souls into entertaining thoughts of violence and totalitarianism. Probably one solution lies in a radical change of vocabulary; the old one (which, lets not forget, was once known as modern) clearly no longer suffices. Those who argued that EDSA represented a better revolutionary paradigm also have a lot of explaining to do for example, why the Marcoses and their minions are back in business as if nothing had happened in 1986. Corollarily, in this runaway world dominated by globalization, the notion that hackers incarnate the post-Marxist idea of global revolution, and the possibility that they might even succeed in endangering the corporate giants and nation-state superpowers of the developed world using strategies more efficient than those deployed by the Marxists, should not be dismissed off hand. Apologists of Marx and Engels still make excuses to the effect that the latter never foresaw the configurations of late 20th century society: although well-meaning, this reasoning effectively shackles the two founding fathers to their 19th century mindset, making them quite useless for contemporary purposes. But isnt that precisely what has happened, in the absence of more convincing arguments? In any event, the times call for a long-delayed clearing of the air around here. After all, Marxists have nothing to lose but their ideological chains.